A Case Series of Myocarditis Following Third (Booster) Dose of COVID-19 Vaccination: Magnetic Resonance Imaging Study - Shiyovich, Arthur; Witberg, Guy; Aviv, Yaron; Kornowski, Ran; Hamdan, Ashraf (Frontiers in Cardiovascular Medicine, 2022)
Background Myocarditis has been reported following the first two doses of Pfizer-BNT162b2 messenger RNA (mRNA) COVID-19 vaccination. Administration of a third dose (booster) of the vaccine was initiated recently in Israel. Objective The aim of this study was to describe the characteristics of patients referred for cardiac magnetic resonance (CMR) imaging with myocarditis following the booster. Methods Patients referred for CMR imaging with a clinical diagnosis of myocarditis within 21 days following the booster, between July 13 and November 11, 2021, were analyzed. Results Overall, 4 patients were included, 3/4 (75%) were men, and the mean age was 27 ± 10 years. The time from booster administration to the onset of symptoms was 5.75 ± 4.8 days (range 2–14). Obstructive coronary artery disease was excluded in 3 of the patients (75%). CMR was performed 34 ± 15 days (range 8-47 days) following the 3rd vaccination. The mean left ventricular ejection fraction was 61 ± 7% (range 53–71%), and regional wall motion abnormalities were present in one of the patients. Global T1 was increased in one of the patients, while focal T1 values were increased in 3 of the patients. Global T2 was increased in one of the patients, while focal T2 values were increased in all the patients. Global ECV was increased in 3 of the patients, while focal ECV was increased in all the patients. Median late gadolinium enhancement (LGE) was 4 ± 3% (range 1–9%), with the inferolateral segment as the most common location (3 of the 4 patients). All the patients met the Updated Lake Louise Criteria. Conclusions Patient characteristics and CMR imaging findings of myocarditis following the administration of the booster vaccine are relatively mild and consistent with those observed with the first two doses. Although larger-scale prospective studies are necessary, these initial findings are somewhat reassuring.